(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Brinjal (Eggplant) is a very common and popular horticultural crop in Bangladesh. This study reports on quantification of farm level postharvest loss of brinjal in two intensive growing districts Jamalpur and Rangpur of Bangladesh. It also outlines the determinants of brinjal postharvest loss and problems of brinjal farmers. A total of 144 farmers were considered for the study from purposively selected four villages. Total postharvest loss was quantified by evaluating quantitative and qualitative losses of brinjal. Farmers were found well acquainted with a range of postharvest practices such as definite point and stage of brinjal harvesting, sorting, grading and packaging. Morning was the most preferred time for harvesting and selling of brinjal in the survey areas. Distance selling and motor driving van for local selling were used by 25% and 23% of the respondents. Physical damage and physical appearance were the two basic criteria for grading of brinjal at farm level. Among the problems, absence of storage and lower prices of brinjal scored highest PFI 208 and 181, respectively from the possible range of 0 to 216. Farm level postharvest loss of brinjal was 13.90% of total production where full damages accounts for 9.16% alone. Infested by insect and rotten were the primary causes of full damages of brinjal in the survey area. The 4.73% of the total postharvest loss was due to partial damages of brinjal where skinning and bruising constitutes the maximum share. Due to postharvest loss brinjal farmers have to incur financial loss of Tk. 709.05 per decimal of brinjal cultivation. Total harvested amount, farmer’s education, packaging and selling place were found significant factors for postharvest loss of brinjal in the survey area. It is recommended that government, research institution and Department of Agricultural Extension (DAE) should work jointly to educate farmers against postharvest loss of brinjal in Bangladesh. J Bangladesh Agril Univ 17(4): 454–460, 2019